2017
DOI: 10.18632/oncotarget.17345
|View full text |Cite
|
Sign up to set email alerts
|

The highly expressed COL4A1 genes contributes to the proliferation and migration of the invasive ductal carcinomas

Abstract: BackgroundInvasive ductal carcinoma is a kind of very typical breast cancer. The goal of our research was to figure out the molecular mechanism of Invasive ductal carcinoma and to find out its potential therapy targets.ResultsThe total amount of 478 differentially expressed genes in Invasive ductal carcinoma which compared with normal breast epithelial cells were recognized. Functional enrichment analysis proved the most part of differentially expressed genes had connection with ECM-receptor interaction. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 36 publications
1
40
0
Order By: Relevance
“…Recently, COL4A1 was reported to be markedly increased and regulated diverse cellular functions such as metabolism, proliferation and protein synthesis through the activation of the PI3K/AKT pathway in urothelial carcinoma . It has also been demonstrated that highly expressed COL4A1 contributed to ductal carcinoma cell proliferation and migration by activating the extracellular matrix receptor in breast tissues . But the function of COL4A1 in gastric carcinoma has not hitherto been well understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, COL4A1 was reported to be markedly increased and regulated diverse cellular functions such as metabolism, proliferation and protein synthesis through the activation of the PI3K/AKT pathway in urothelial carcinoma . It has also been demonstrated that highly expressed COL4A1 contributed to ductal carcinoma cell proliferation and migration by activating the extracellular matrix receptor in breast tissues . But the function of COL4A1 in gastric carcinoma has not hitherto been well understood.…”
Section: Discussionmentioning
confidence: 99%
“…33 It has also been demonstrated that highly expressed COL4A1 contributed to ductal carcinoma cell proliferation and migration by activating the extracellular matrix receptor in breast tissues. 34 But the function of COL4A1 in gastric carcinoma has not hitherto been well understood. Thus far, this study reported that COL4A1 was overexpressed and associated with a poor prognosis in gastric carcinoma by bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were exposed to drug treatment for indicated time and lysed in RIPA buffer as detailed in previous report [32]. Lysate was mixed with sample loading buffer and heated at 100oC for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…4A and B). 7,14,43,46 In contrast, nonfluorescent samples expressed genes associated with mature cells of the central nervous system such as MOBP, MAL, and OPALIN ( Fig. 4A and C).…”
Section: Intraoperative 5-ala-induced Fluorescence In Gbm Specimens Imentioning
confidence: 99%